Progenitor Diversity in the Accreted Stellar Halos of Milky Way–like Galaxies - Sy-Yun Pu; Andrew P. Cooper; Robert J. J. Grand; Facundo A. Gómez; Antonela Monachesi (The Astrophysical Journal)
Ongoing large stellar spectroscopic surveys of the Milky Way seek to reconstruct the major events in the assembly history of the Galaxy. Chemical and kinematic observations can be used to separate the contributions of different progenitor galaxies to the present-day stellar halo. Here, we compute the number of progenitors that contribute to the accreted stellar halos of simulated Milky Way–like galaxies as a function of radius (the radial diversity) in three suites of models: Bullock & Johnston, Aquarius, and Auriga. We show that there are significant differences between the predictions of these three models, beyond the halo-to-halo scatter expected in ΛCDM. Predictions of diversity from numerical simulations are sensitive to model-dependent assumptions regarding the efficiency of star formation in dwarf galaxies. We compare, at face value, to current constraints on the radial diversity of the Milky Way's accreted halo. These constraints imply that the halo of our Galaxy is dominated by ∼2 progenitors in the range 8–45 kpc, in contrast to averages of 7 progenitors in the Bullock & Johnston models, 3.5 in Aquarius, and 4.2 in Auriga over the same region. We additionally find that the models with radial diversity most similar to that of the Milky Way are predominantly those with ongoing merger events. The Milky Way therefore appears unusual in having an accreted stellar halo dominated by a small number of progenitors accreted at very early times.